Training Specificity of Inspiratory Muscle Training Methods: A Randomized Trial - Van Hollebeke, Marine; Gosselink, Rik; Langer, Daniel (Frontiers in Physiology, 2020)
Introduction: Inspiratory muscle training (IMT) protocols are typically performed with mechanical threshold loading with inspirations initiated from residual volume (MTL-RV). MTL initiated from functional residual capacity (MTL-FRC) or tapered flow resistive loading initiated from RV (TFRL-RV) might improve respiratory muscle function over a larger range of lung volumes. We aimed to compare effects of three different IMT protocols all using intermediate flow and pressure loads on maximal inspiratory pressures (PImax) and maximal inspiratory flow rates (V̇Imax) at three different lung volumes. Methods: 48 healthy volunteers (age: 48±9years, 42% male, PImax: 110±28%pred) were randomly assigned to perform three daily sessions of either MTL-RV, MTL-FRC or TFRL-RV IMT for 4 weeks. Sessions consisted of 30 breaths against the highest tolerable load. Before and after the training, PImax was measured at RV, FRC and midway between FRC and TLC (FRC-TLC). V̇Imax was measured at the same lung volumes against a range of external threshold loads (no load, 20, 30, 50 and 70% of PImax baseline). Results: PImax improved significantly at all lung volumes with MTL-FRC and TFRL-RV but only at RV and FRC after MTL-RV. No significant improvements in V̇Imax were observed after MTL-RV. Improvements in V̇Imax were significantly larger after TFRL-RV at all lung volumes and after MTL-FRC at higher lung volumes (FRC and FRC-TLC) in comparison with MTL-RV. Conclusion: Only TFRL-RV and MTL-FRC training resulted in consistent improvements in respiratory muscle function at higher lung volumes, whereas improvements after MTL-RV were restricted to gains in PImax at lower lung volumes. Further research is warranted to investigate whether the observed differences translate into differential changes in respiratory muscle endurance and respiratory muscle function during exercise.